Rearticulating the promotion of Japanese language and culture from the perspective of “soft power”: planning and effects - Gu, Jingshu; Deng, Shiping (Frontiers in Psychology, 2024)
The concept of soft power has engendered lively discourse within the international community. The development of a nation’s soft power frequently hinges on cultural communication and the promotion of language. This manuscript concentrates on Japan as a case study and undertakes an investigation of the methods it has employed to cultivate its soft power. To accomplish this objective, Japan’s strategies for cultural communication and the promotion of the Japanese language are comprehensively examined. From the perspective of language planning, prestige planning of language and culture constitutes a crucial mode of cultural communication, whereas language education planning (or acquisition planning) is the primary method of language promotion. Japan has adeptly disseminated its culture overseas through cultural communication and language promotion. On one hand, it fashions a “cool culture” embodied by anime and manga to augment cultural appeal and amplify national image. On the other hand, it advances the Japanese language abroad by establishing supportive institutions, dispatching experts and volunteers, and creating online teaching materials. Building on Japan, this paper establishes a theoretical framework for the construction of soft power, employing the aforementioned two approaches as valuable guides for research on soft power.